The mutiny on board HMS Bounty - Bligh, William 1754-1817 (Great illustrated classics, 1992)
Captain William Bligh recounts his experiences in 1789 when his ship "Bounty" was taken over in a mutiny and he and a crew of eighteen men were set adrift in an open boat in the southern Pacific Ocean.